Toxoplasma gondii gra5 deletion mutant protects hosts against Toxoplasma gondii infection and breast tumors - Chen, Min; Yang, Pei; Xin, Zixuan; Chen, Jiating; Zou, Weihao; Zhou, Lijuan; Yang, Lili; Peng, Jiao; Peng, Hongjuan (Frontiers in Immunology, 2023)
Toxoplasma gondii is the causative agent of toxoplasmosis, a zoonotic disease that poses a threat to human health and a considerable loss to livestock farming. At present, clinical therapeutic drugs mainly target T. gondii tachyzoites and fail to eradicate bradyzoites. Developing a safe and effective vaccine against toxoplasmosis is urgent and important. Breast cancer has become a major public health problem and the therapeutic method needs to be further explored. Many similarities exist between the immune responses caused by T. gondii infection and the immunotherapy for cancers. T. gondii dense granule organelles secrete immunogenic dense granule proteins (GRAs). GRA5 is localized to the parasitophorous vacuole membrane in the tachyzoite stage and the cyst wall in the bradyzoite stage. We found that T. gondii ME49 gra5 knockout strain (ME49Δgra5) was avirulent and failed to form cysts but stimulated antibodies, inflammatory cytokines, and leukocytes infiltration in mice. We next investigated the protective efficacy of ME49Δgra5 vaccination against T. gondii infection and tumor development. All the immunized mice survived the challenge infection of either wild-type RH, ME49, VEG tachyzoites, or ME49 cysts. Moreover, ME49Δgra5 tachyzoite inoculation in situ attenuated the growth of murine breast tumor (4T1) in mice and prevented 4T1’s lung metastasis. ME49Δgra5 inoculation upregulated the levels of Th1 cytokines and tumor-infiltrating T cells in the tumor microenvironment and triggered anti-tumor responses by increasing the number of natural killer, B, and T cells, macrophages, and dendritic cells in the spleen. Collectively, these results suggested that ME49Δgra5 was a potent live attenuated vaccine against T. gondii infection and breast cancer.